Ekonomi Kreatif Kerajinan Eceng Gondok Di Desa Cihampelas Sebagai Sumber Belajar IPS - Annisa Jauhar Fadhilah (Pendidikan IPS FKIP ULM, 2023)
Social studies teachers often rely on conventional learning resources, primarily textbooks, including electronic books, and student worksheets available in the library. The utilization of varied learning resources by teachers is relatively limited. Therefore, this study aims to achieve four objectives: 1) Describe the home industry of water hyacinth crafts. 2) Explore the connection between water hyacinth crafts and the creative economy of the Cihampelas village community. 3) Investigate the integration of home industry water hyacinth crafts as social studies learning resources. 4) Identify the challenges faced by the home industry of water hyacinth crafts in contributing to the creative economy and propose solutions for their utilization as social studies learning resources. This research adopts a descriptive qualitative approach and is conducted in Cihampelas Village. The findings reveal that the process of incorporating the water hyacinth craft home industry as an environmentally-based learning resource involves social studies teachers initially analyzing the relevant educational standards before conducting field visits. For instance, in the case of Class IX, Basic Competency 3.3, which focuses on the development of creative economies based on the regional potential for community welfare, the material can be linked to the local environment, such as Cihampelas Village's utilization of water hyacinth crafts derived from the Saguling reservoir, contributing to the community's creative economy. This approach ensures the relevance of the activities to the water hyacinth craft home industry in Cihampelas Village.